How to Examine the Nervous System - Ross, Robert T. (Humana Press : Imprint: Humana, 2006)
Now reissued by popular demand, this acclaimed and seminal textbook by one of North America's most respected neurologists simplifies the apparent complexity of the neurological examination to make it completely understandable and satisfying to perform. With simple prose and numerous helpful illustrations, the author describes in detail reliable bedside examination techniques that will pinpoint the location of a lesion in the nervous system and lead to a resolution of the problem. The techniques cover a wide variety of problem areas, including the visual pathways, the sensory system, upper motor neurons, cranial nerves, the cerebellar system, upper and lower limbs, reflexes, the corticospinal system, disorders of speech, and problems of stance, gait, and balance. Classic and didactically inspired, How to Examine the Nervous System, Fourth Edition provides both established physicians and beginning medical students a concise, user-friendly introduction to the methods and techniques for study of the nervous system, showing that the examination is readily performed, that it is rationally constructed, and that it can be carried out successfully.